(untitled) (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2005)
Abstract The network structure of Humboldt’s American travel journals with emphasise on the bibliographic background is investigated on the basis of O. Ette’s concept of Humboltian writing. The complexity of Humboldt’s writing is shown in the following dimensions: splitting up into disciplines, hypertext structure of singular texts, multilinguality, connections to Humboldt’s oeuvre and correspondence, Humboldt’s network in the scientific community. This specific structure cannot be fully understood in a strictly linear reading (which is what a regular book asks for), especially because of the lack of a new indexed edition of his travelogues. Therefore, a digital library could be an adequate medium to represent Humboldt’s scientific writing and, consequently, for his specific organisation of knowledge. Zusammenfassung Ausgehend von O. Ettes Analyse des Begriffs Humboltian writing wird unter Betonung des bibliographischen Hintergrunds die vernetzte Struktur des amerikanischen Reisewerks Alexander von Humboldts dargestellt. Die Komplexität seines Schreibens zeigt sich in mehreren Dimensionen: disziplinäre Aufsplittung, Hypertextstruktur der einzelnen Texte selbst, Multilingualität, Vernetzung mit anderen Werken Humboldts und seinem epistolarischen Nachlaß, sein wissenschaftliches Netzwerk in der scientific community. Diese Struktur wird bei einer rein linearen Lesart (die ein normales Buch nur zuläßt) nicht vollständig wahrgenommen, zumal es bisher keine mit Registern versehene Neuedition seines Reisewerks gibt, so daß eine digitale Bibliothek ein adäquates Medium für die Darstellung des Humboldtschen Schreibstils und gleichzeitig der für ihn typischen Organisation des Wissens sein könnte. Resumen Partiendo del análisis del concepto Humboltian writing de O. Ette, se presenta, enfatizando el trasfondo bibliográfico, la estructura interrelacionada de la relación de viaje de Alexander von Humboldt. La complejidad de sus escritos se aprecia en varios dimensiones: separación de disciplinas, hiperestructura de cada texto en sí, multilingualidad, interrelación con otras obras de Humboldt y con su legado epistolar, su red académico en la “scientific community“. Esta estructura no se aprecia plenamente a lo largo de una lectura lineal (que un libro común solamente permite) – además que no existe hasta ahora una nueva edición de su relación de viaje que contenga índices – lo que permitiría concebir la biblioteca digital como un medio adecuado para la presentación simultánea del estilo de escritura humboldtiano y de su típica organización del saber.